IS THE INDONESIAN MARKET REACT TO THE SUKUK ISSUANCE ANNOUNCEMENT ? - Ridwan, Muhammad Qomaruddin; Barokah, Zuni (Riset Akuntansi dan Keuangan Indonesia, 2022)
This study aims to examine the market reaction following the announcement of sukuk issuance by companies listed on the Indonesia Stock Exchange between 2013 and 2017. During this period, there were 23 sukuk publishing announcements as samples for this study. Although two events led to the issuance of sukuk, there have been no unusual returns overall. There was no change in trading volume on the day before and after the announcement of the sukuk issuance, both as a whole and for each event. To that end, we cannot find any significant association between the type of sukuk (i.e., ijarah) and the not related to cumulative abnormal returns.